Performance and emission characteristics of turbocharged diesel engine fueled with palm biodiesel blends - Yang, Byungmo; A. Kalam, M; Cho, Haengmuk (International Journal of Engineering and Technology, 2018)
The exhaustion of fossil fuels and sharp rise in crude oil prices has led to the development of various alternative fuels. Alternative fuels are a necessity to meet rising energy consumption rates and to ensure eco-friendly growth. Alternative fuels that can be regenerated, are sustainable and have clean burning capacity to help promote an eco-friendly development. Whereas there have been various ideas and technologies relating to biodiesel as an alternative fuel, these tend to be restricted to the distant future insofar as compression-ignition engines are concerned. Biodiesel, produced by reacting triglycerides which are the main component of animal or plant-based fatty acids with methanol, is known to be an eco-friendly alternative fuel that can take the place of conventional petroleum diesel. In the present study, biodiesel (palm oil) was mixed at a certain ratio with commercially sold diesel, then introduced into a TCDI engine which was run at low load conditions for engine performance and exhaust gas measurement. Both engine output and torque were reduced, and fuel consumption increased to make up for the reduction in output. There were slight reductions in NOx and CO2 emissions, but changes in CO and HC emissions were negligible.Â Â